Port security poster, 1940-1945
1947 1939-1945 "Port security poster, 1940-1945" [HFR0174], c. 1940-1945 This poster warns war workers in docks and ports against gossip and careless talk which might leak defence secrets relating to shipping convoys to enemy spies.